The Optimal Size of Hedge Funds: Conflict between Investors and Fund Managers - YIN, CHENGDONG (Journal of Finance, 2016)
ABSTRACT This study examines whether the standard compensation contract in the hedge fund industry aligns managers’ incentives with investors’ interests. I show empirically that managers’ compensation increases when fund assets grow, even when diseconomies of scale in fund performance exist. Thus, managers’ compensation is maximized at a much larger fund size than is optimal for fund performance. However, to avoid capital outflows, managers are also motivated to restrict fund growth to maintain style‐average performance. Similarly, fund management firms have incentives to collect more capital for all funds under management, including their flagship funds, even at the expense of fund performance.